CIVIL LAW ANALYSIS OF UNWRITTEN AGREEMENTS IN BUSINESS ACTIVITIES - Ega Nabilasari Lesmana; Dewa Gede Pradnyana Yustiawan (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
In traditional societies, unwritten contracts were frequently used for commercial transactions. Unwritten agreements are weaker than written ones, particularly when it comes to proving their existence in the event of a dispute. The aim of this article was to conduct an analysis of unwritten agreements in civil law and to evaluate the advantages and disadvantages of forming and implementing such agreements. This is a normative legal research which focuses on positive law inventory, legal principles and doctrine, legal discovery in in concrete cases, legal systematics, level of synchronization, comparative law and legal history. In the deliberation, a verbal agreement was considered valid under civil law so long as it did not contradict Article 1320 of the Civil Code. The existence of a verbal agreement was also supported by the principle of contract freedom, which allowed the parties to determine the form of the agreement. Unwritten agreements were advantageous in terms of the amount of time required to reach an agreement and the use of trust in the formulation and implementation of the agreement, but they lacked the ability to be proven in the event of a dispute.